EFFECT OF PARTICIPATIVE BUDGETING ON BUDGETARY SLACK WITH ASYMMETRY INFORMATION, LEADERSHIP STYLE AND ORGANIZATIONAL COMMITMENT AS MODERATION VARIABLES - Putu Kepramareni; I Gusti Ayu Asri Pramesti; Sri Widiasih (Unmas Press, 2019)
The purpose of this study was to determine the effect of budget participation on budgetary slack, the effects of information asymmetry, leadership style and organizational commitment on the relationship between budget participation on budgetary slack. The population was 9 bureaus in the Regional Secretariat of the Province of Bali with 145 numbers of respondents consisting of the head of the bureau, the head section of the bureau, and the head of the sub-section of the bureau involved in preparing the budget. Sample technique used is purposive sampling. The analysis technique used is moderated regression analysis (MRA). The results Obtained in contribution budget that had a positive effect on budgetary slack, information asymmetry was Able to strengthen the effect of budget participation on budgetary s lack, and leadership style and organizational commitment weakened weaken the influence of budget participation on budgetary slack.